MODERASI GOOD CORPORATE GOVERNANCE PADA PENERAPAN GREEN ACCOUNTING DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP FIRM VALUE - Lestara Permana, Gusi Putu; Ni Putu Suryawati; Ketut Tanti Kustina; Putu Purnama Dewi (Universitas Prof.Hazairin,SH Bengkulu, 2024)
This study aims to evaluate the influence of Good Corporate Governance (GCG) as a moderating factor in the context of Firm Value, focusing on the application of Corporate Social Responsibility (CSR) and Green Accounting among mining firms listed on the Indonesia Stock Exchange for the period from 2020 to 2023. A sample of 124 mining companies was determined through purposive sampling techniques. Data analysis was performed utilizing Partial Least Squares (PLS) software. The results demonstrate that there is no significant effect of Green Accounting on Firm Value, while CSR has a positive effect. Furthermore, it has been established that GCG successfully moderates the relationship between Green Accounting and Firm Value, along with the connection between CSR and Firm Value. The theories and models used in this research adequately assess the variables concerning Green Accounting, CSR, and Firm Value